Kawasaki Disease in Infants in the First 3 Months of Age in a Mexican Population: A Cautionary Tale - Garrido-García, Luis Martín; Gutiérrez-Alanis, Juan Humberto; Ramírez-Perea, Ana Isabel; Tremoulet, Adriana; Yamazaki-Nakashimada, Marco Antonio (Frontiers in Pediatrics, 2020)
Background: Kawasaki disease (KD) is an acute febrile illness that largely affects young children before 5 years of age. Younger children with KD are reported to have a higher prevalence of coronary artery abnormalities. Little is known about infants in the first 3 months of age diagnosed with KD. Methods: A retrospective study was conducted at the National Institute of Pediatrics in Mexico City from 1995 to 2019. Clinical features, laboratory results and cardiac outcomes were recorded. Infants in the first 3 months of age were compared with older patients. Wilcoxon-Mann-Whitney analysis was performed for continuous variables and Fisher's exact test for categorical variables. Results: Six hundred and eighty-eight cases of KD were included in this study. Fourteen cases were diagnosed in the first three months of age. Heart failure and KD shock-syndrome was found in five cases (35.7%). Giant coronary artery aneurysms were found in six cases in the younger group (42.9%). Conclusions: Diagnosis of KD in children younger than 3 months of age is rare. In most cases, an incomplete presentation contributed to a delay diagnosis, treatment, and complications. Younger patients with KD have an increased risk of presenting cardiac complications, including giant coronary artery aneurysms, shock, and death.